THE UNDERGRADUATE ACCOUNTING CURRICULUM. - Pye, Malcolm L. (The Accounting Review, 1955)
The article discusses generally acceptable objectives formulated to guide the development of course content, instruction, and curricula for the undergraduate program in accounting. These can be checked for validity by applying the test of reasonableness. This is a widely used accounting test, particularly in cost distributions. This same test is used to evaluate the pronouncements of the Research Committees of the American Institute of Accountants. The Standards Rating Committee has proposed a four-year program, while many hold the viewpoint that either five-year courses, or four years of undergraduate work, and one year of graduate work, are necessary for adequate training. The committee apparently favors a five-year program, but at the same time recognizes the inherent difficulty of such at this time. Specialization is necessary but not at the undergraduate level. A broad foundation will enable the student to become a better specialist. The failure to provide a means which will enable the student to integrate the many ideas received in diverse courses is another deficiency.